State ownership and nationalization in energy sector: The case of Kazakhstan's oil industry - Serik Orazgaliyev (Asian Development Bank Institute (ADBI), 2019)
State-owned enterprises (SOEs) have been declining in numbers in most industries. However, in the oil and gas industry, state-owned national oil companies (NOCs) continue to secure dominant positions in most of the oil-producing countries. In some instances, energy-exporting countries conducted nationalization of their resources, while in other cases they tightened control over the privately owned firms. This paper begins with broader questions of why countries choose to have state-owned enterprises and why energy-rich states prefer to nationalize their oil and gas industries. Next, this paper explores a case of nationalization policies in Kazakhstan's oil and gas industry in the post-Soviet period. Although the full nationalization of the energy sector had not happened, the government's intervention in the industry had become more pervasive. As a result, multinationals were forced to form partnerships with the domestic national oil company (NOC), KazMunaiGas, in major oil and gas projects. We further explore the role of KazMunaiGas NOC in Kazakhstan's hydrocarbon sector. At the beginning of the 2000s, Kazakhstan consolidated its dispersed state-owned enterprises in the energy sector to create KazMunaiGas. Since then, Kazakhstan has set an objective to ensure more active participation of the domestic NOC in big-scale energy projects. Although KazMunaiGas was shaped as a fully integrated NOC with an increasingly visible role in the industry, it has to deal with challenges that many NOCs face globally. These challenges include improving technological capabilities, access to capital and financial independence, as well as strategic human resource management.
Keywords: Z18; F52; H11; 330; state ownership; nationalization; oil sector; national oil company; Kazakhstan